Causal Effect of Corporal Punishment on Children's Internalizing and Externalizing Behavioral Outcomes: Results from a Propensity Score Matching Analysis - Morris, Sara Zane (2007)
Substantial research supports the association between corporal punishment and children's behavioral problems, suggesting that punishment leads to both internalizing and externalizing behaviors. However, this research has not been able to discern the direction of causality in this relationship for many reasons, including a lack of experimental data. The purpose of this study is to assess the causal effect of corporal punishment on internalizing and externalizing behaviors by using a Propensity Score Matching (PSM) analysis. This study uses data from waves 1 and 2 of the longitudinal cohort study of the Project on Human Development in Chicago Neighborhoods (PHDCN), including 6, 9, 12, and 15 year old cohorts. Results reveal two major findings as they relate to the effects of corporal punishment on children's behavioral outcomes. First, results show that a large amount of selection bias exists before matching occurred. Second, once matching was implemented no causal effect remained for corporal punishment on the proposed outcome measures. Limitations and ways of overcoming them in future research are also discussed